Factors Influencing Patient Conveyance Decisions by Ambulance Service Responders - Hassan Farhat (9000509) (2024)
Background The Ambulance Service in Qatar often receives 999 emergency calls that do not necessarily result in patient transportation to a medical facility. This study aimed to comprehensively examine the various elements affecting patient conveyance decisions in Qatar during 2023, focusing on socio-cultural influences, clinical uncertainties, and operational aspects. Methods A retrospective, quantitative analysis was conducted on a data set comprising 93,712 emergency calls made to the Hamad Medical Corporation Ambulance Service (HMCAS) 999 emergency medical dispatch centre from January to May 2023. "Handover", the outcome variable (patient transported or not), and other predictors like socio-demographics and clinical information were assessed. Analytical techniques were utilised, including heatmaps (aggregated tabular representation of transportation decision outcomes based on various factors) and scatter plots (graphical representation over time of various parameters). Results In this study, 23.95% (N=21,194) of the emergency calls did not result in patient transportation to a medical facility, whilst 76.05% (N=67,285) led to patient conveyance. Heatmaps (Figure 1) demonstrated significant differences in demographic variables between the transported and non-transported groups and the dispatch types. Scatter plots (Figure 2) showed that the median response time aligns with international benchmarks. Conclusion The study sheds light on the intricate variables affecting pre-hospital patient conveyance decisions in Qatar. Patterns such as male dominance and specific timing for EMS activities were noted, underlining the need for a comprehensive patient assessment that goes beyond medical histories. Additional investigations are needed to examine the duration spent with the patient until the ambulance becomes available for another 999 call. The findings prompt further analysis, research, and innovative approaches to enhance the standards of pre-hospital care delivery.